Spór o przyszłość literatury polskiej, czyli polemiki ze Stefanem Żeromskim po jego odczycie Literatura a życie polskie - Olszewska, Maria Jolanta (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2019)
The discussion concerns the article Literatura a życie polskie [Literature and Polish Life] of Stefan Żeromski delivered on 28 of August 1915 in Zakopane. Under the influence of World War I events his views changed. Żeromski, the writer recognized as the conscience of the nation, in his lecture put a question regarding the contribution of literature to Polish independence. In his opinion the autonomy of literature depends on the conditions in which it arises and is perceived. Thus the freedom of art is a prerequisite for the liberation of the nation. This is very important from the perspective of community life. This lecture caused a heated discussion with the participation of polish eminent representatives of intellectual life. This dispute turned out to be one of the most important discussions in this time in the perspective of resurrecting of Polish statehood.
A dispute over the future of Polish literature, that is, polemics with Stefan Żeromski after his article Literatura a życie polskie